Journey of Medical Education Department, BCPS: Its Contribution in Developing Skilled Fellows for Effective use of Assessment Tools (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not availableJ Bangladesh Coll Phys Surg 2022; 40: 107-109